Ex‐Vivo MRI of the Normal Human Placenta: Structural–Functional Interplay and the Association With Birth Weight. Issue 1 (19th November 2021) - Link‐Sourani, Daphna; Avisdris, Netanell; Harel, Shaul; Ben‐Sira, Liat; Ganot, Tuvia; Gordon, Zoya; Many, Ariel; Ben Bashat, Dafna
Abstract : Background: Advanced magnetic resonance imaging (MRI) methods are increasingly being used to assess the human placenta. Yet, the structure–function interplay in normal placentas and their associations with pregnancy risks are not fully understood. Purpose: To characterize the normal human placental structure (volume and umbilical cord centricity index (CI)) and function (perfusion) ex‐vivo using MRI, to assess their association with birth weight (BW), and identify imaging‐markers for placentas at risk for dysfunction. Study Type: Prospective. Population: Twenty normal term ex‐vivo placentas. Field Strength/Sequence: 3 T/ T1 and T2 weighted (T1 W, T2 W) turbo spin‐echo, three‐dimensional susceptibility‐weighted image, and time‐resolved angiography with interleaved stochastic trajectories (TWIST), during passage of a contrast agent using MRI compatible perfusion system that mimics placental flow. Assessment: Placental volume and CI were manually extracted from the T1 W images by a fetal‐placental MRI scientist (D.L., 7 years of experience). Perfusion maps including bolus arrival‐time and full‐width at half maximum were calculated from the TWIST data. Mean values, entropy, and asymmetries were calculated from each perfusion map, relating to both the whole placenta and volumes of interest (VOIs) within the umbilical cord and its daughter blood vessels. Statistical Tests: Pearson correlations with correction for multiple comparisons using false discovery rate were performed between structural and functional parameters, and with BW, with P  < 0.05 considered significant. Results: All placentas were successfully perfused and scanned. Significant correlations were found between whole placenta and VOIs perfusion parameters (mean R  = 0.76 ± 0.06, range = 0.67–0.89), which were also significantly correlated with CI (mean R  = 0.72 ± 0.05, range = 0.65–0.79). BW was correlated with placental volume ( R  = 0.62), but not with CI ( P  = 0.40). BW was also correlated with local perfusion asymmetry ( R  = −0.71). Data Conclusion: Results demonstrate a gradient of placental function, associated with CI and suggest several ex‐vivo imaging‐markers that might indicate an increased risk for placental dysfunction. Level of Evidence: 1 Technical Efficacy: Stage 1